2017
DOI: 10.1016/j.cej.2016.10.077
|View full text |Cite
|
Sign up to set email alerts
|

Direct Cr (VI) bio-reduction with organics as electron donor by anaerobic sludge

Abstract: Industrial activities produce lots of Cr (VI)-containing wastewater. This study presented a detailed work on direct Cr (VI) bio-reduction (i.e. Cr (VI) is reduced with organics as electron donor directly) by anaerobic sludge through both batch and long-term experiments. Effects of pH and initial Cr (VI) concentrations on direct Cr (VI) bioreduction activity were evaluated. The highest direct Cr (VI) bio-reduction rate was

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(18 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“… Lu et al (2020) found that natural material, mackinawite, could be effectively operated as electron donors by a neutrophilic chemoautotroph, Acidovorax in a batch bioreactor, and the intermediate microbial physiological constituents, VFAs, released from mineral bio-oxidation, could enable the shuttle of electrons to Cr(VI) involving a reducer like Geobacter . In an up-flow anaerobic sludge bed reactor, the population of genus Trichococcus greatly increased toward the operation period of Cr(VI) reduction using anaerobic sludge, which mainly attributed to fermentation of organic complexes to be available as electron donors, where genera like Desulfovibrio , Ochrobactrum , and Anaerovorax were the main Cr(VI) reducers ( Qian et al, 2017 ). Anaerobic digestion using various electron donors have shown high efficiency of Cr(VI) reduction in different bioreactors ( Wang et al, 2018 ; Zheng et al, 2019 ).…”
Section: Role Of Various Chemical Additives In Ex Situ mentioning
confidence: 99%
“… Lu et al (2020) found that natural material, mackinawite, could be effectively operated as electron donors by a neutrophilic chemoautotroph, Acidovorax in a batch bioreactor, and the intermediate microbial physiological constituents, VFAs, released from mineral bio-oxidation, could enable the shuttle of electrons to Cr(VI) involving a reducer like Geobacter . In an up-flow anaerobic sludge bed reactor, the population of genus Trichococcus greatly increased toward the operation period of Cr(VI) reduction using anaerobic sludge, which mainly attributed to fermentation of organic complexes to be available as electron donors, where genera like Desulfovibrio , Ochrobactrum , and Anaerovorax were the main Cr(VI) reducers ( Qian et al, 2017 ). Anaerobic digestion using various electron donors have shown high efficiency of Cr(VI) reduction in different bioreactors ( Wang et al, 2018 ; Zheng et al, 2019 ).…”
Section: Role Of Various Chemical Additives In Ex Situ mentioning
confidence: 99%
“…Their corresponding percentages removal were 87.87% at 600 mg/m 3 .d, 94.22 % at 1800 mg/m 3 .d, 92.25 % at 3000 mg/m 3 .d and 98.47 % at 6000 mg/ m 3 .d. Results can be explained that reduction process induced by hexavalent chromium in the presence of biological sulfidogenesis was carried out by SBR (Desulfobacter, Desulfobulbus and Desulfovibrio) [15]. Figure 3 shows that the maximum Cr (VI) reduction rate was 3.95 mg Cr (VI)/L/h and this is in presence of mixed sludge culture formed from anaerobic sludge and the hydrogen sulfide produced in the H-UASB which stimulate the SBR to reduce Cr (VI) into Cr (III).…”
Section: Performance Of the H-uasb Inoculated With Different Concentrmentioning
confidence: 99%
“…In H-UASB, the pH ranges from 6.5-8.5 and Cr (VI) can exist as which is reduced directly to Cr (III) by SRB and chromate reducing bacteria using the organic matter as an electron donor and chrome hydroxide sediment is formed on the surface of the microorganisms as indicated in equation 4. Qian et al [15] showed that possesses similar bioactivity like because they have similar structure (four tetrahedrally arranged oxygen atoms and two negative charges).…”
Section: Fig 3 Removal Rate Of Cr (Vi) At Different Concentrationsmentioning
confidence: 99%
“…Recently, several researchers verified that mixed sludge that enriched microbial population could reduce chromium polluting potential, thus avoiding the high cost of strain cultivating [18][19][20]. These studies overcame the weaknesses of the poor adaptability of the single strain in the field environmental conditions [17].…”
Section: Introductionmentioning
confidence: 99%